Research on Vehicle Following and Overtaking Safety Distance Models Considering Trust Level of Driving - Wencai Sun; Xinze Liu; Shiwu Li; Xue Wen (Journal of Advanced Transportation)
To investigate the influence of drivers’ cognitive differences on the vehicle driving process, this paper focuses on the mechanism of drivers’ cognition of vehicles, roads, and environments. Existing studies of vehicle following and overtaking usually set the driver reaction time, vehicle braking deceleration, and acceleration as fixed values, ignoring the individual differences of drivers and their influence by road conditions. Therefore, firstly, the concept of “trust level of driving” is proposed and real vehicle tests and simulator tests for different drivers and different working conditions are designed to quantify the trust level of driving. Addressing the limitations of existing car-following and overtaking models, a safety distance model and a two-way dual-lane highway overtaking model are developed based on trust level of driving. Finally, the driving simulator is used to create scenarios, and the effectiveness of the model is verified. The safe vehicle distance and overtaking distance required by drivers with different trust levels of driving are obtained, and their applicability is explained. In this study, a more accurate and humanized model of safe distance and overtaking was developed to help address driver cognitive deficits and improve traffic safety.